Thematic Kampung Program Implementation in Kampung Jajanan Tradisional and Kampung Jahe Semarang City - Ashar, Ravi Fauzan; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
This study analyzes the factors that determine success in the Thematic Village Implementation Program in the Kampung Traditional Snacks and Ginger Village in Semarang City, using a combination of two implementation model theories namely George C. Edwards III and Merilee S. Grindle. This research is a qualitative descriptive study in Traditional Snack Village, Pudak Payung Village and Kampung Jahe, Pleburan Village, Semarang City. The informants used were the Head of the Social Planning Sub-Division of Semarang City Regional Development Planning Agency, Central Java Indonesian Architects Association (IAI), Staff of Pudak Payung Village, Pleburan Village Staff, Community Groups in Traditional Hawaiian Village Pudak Payung Village, and Chairperson of RW 02 Pleburan Village . Data types: primary and secondary data with data collection techniques: interviews, observation, and documentation studies. Data Analysis and Interpretation is done through Data Reduction, Data Display, and Decision Making and Verification. The technique of testing the validity of data is the triangulation technique. The results showed that the determinants of the implementation of this thematic village were: Communication factors went well, social and cultural economic changes in a better direction, encouraged the welfare of the community, and won from the role allocated by well-done resources. Suggestions that can be given: Communication must be maintained, the types of benefits must be harmonized, cooperation will be held again, and the stakeholders' responses and responsibilities that are already good are expected to be carried out.